Corrosion Control by using Ca(OH)2 and CO2 in Water Distribution Systems - Lee, Dongchan; Lee, Yoonjin; Nam, Sangho (Asian Journal of Chemistry, 2010)
This study was performed to evaluate the application of controlling methods for corrosive water quality in water supply systems. Among the chemicals Ca(OH)2, NaHCO3, NaOH and Na2CO3, Ca(OH)2 were the most effective for controlling alkalinity, pH and calcium concentration in the supplied water. The level of Fe, Zn and Cu in non-treatment pipes appeared to be 1.3, 1.4 and 1.4 times higher than conditions treated with Ca(OH)2 and CO2 in carbon steel, galvanized steel, copper pipe plumbing systems, respectively. The corrosion rate was effectively decreased with the treatment of Ca(OH)2 and CO2 in the pipe systems. The main components of the scale layer were iron and zinc which were 95.9 and 89.2 % for carbon steel and galvanized pipes in the Ca(OH)2 and CO2 treated pipe system, respectively. The substance of calcium in the layer was analyzed to be about 1.9, 1.1 % for carbon steel and galvanized pipes with the treatment of Ca(OH)2 and CO2.